Discover chemistry 2.0 - Appling, Jeffrey R.; Frank, David L. ([S.l.] : Brooks/Cole, 1999)
Teaches general chemistry concepts, including atoms, molecules, gases, liquids, solids, solutions, reactions, equilibrium, acids and bases, thermodynamics, electrochemistry and kinetics
System requirements : IBM PC compatible, 386 DX2 (486 recommended), 33 Mhz processor, Windows 95 or 98, 8MB RAM (16MB for Web), 2X (4Xrecommended) CD-ROM drive
Keywords: Chemistry